Daily HIV pre-exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate-emtricitabine reduced Streptococcus and increased Erysipelotrichaceae in rectal microbiota. Issue 1 (December 2018) - Dubé, Michael; Park, Sung; Ross, Heather; Love, Tanzy; Morris, Sheldon; Lee, Ha
Abstract Daily PrEP is highly effective at preventing HIV-1 acquisition, but risks of long-term tenofovir disoproxil fumarate plus emtricitabine (TDF-FTC) include renal decline and bone mineral density decrease in addition to initial gastrointestinal side effects. We investigated the impact of TDF-FTC on the enteric microbiome using rectal swabs collected from healthy MSM before PrEP initiation and after 48 to 72 weeks of adherent PrEP use. The V4 region of the 16S ribosomal RNA gene sequencing showed thatStreptococcus was significantly reduced from 12.0% to 1.2% (p = 0.036) andErysipelotrichaceae family was significantly increased from 0.79% to 3.3% (p = 0.028) after 48–72 weeks of daily PrEP.Catenibacterium mitsuokai, Holdemanella biformis andTuricibacter sanguinis were increased within theErysipelotrichaceae family andStreptococcus agalactiae, Streptococcus oralis, Streptococcus mitis were reduced. These changes were not associated with host factors including PrEP duration, age, race, tenofovir diphosphate blood level, any drug use and drug abuse, suggesting that the observed microbiome shifts were likely induced by daily PrEP use. Long-term PrEP resulted in increases ofCatenibacterium mitsuokai andHoldemanella biformis, which have been associated with gut microbiome dysbiosis. Our observations can aid in characterizing PrEP's side effects, which is likely to improve PrEP adherence, and thus HIV-1 prevention.